EXPERIMENTAL STUDY OF BEAM-COLUMN BENDING JOINTS WITH VARIOUS TYPES OF COLD ROLLED STEEL CONNECTIONS - Roro Sulaksitaningrum, Setya Nugraha Pratama (BANGUNAN, 2022)
Abstract: Cold rolled steel (cold formed steel) is very often used in the field of construction in today's era. However, in its use there are several drawbacks in the use of cold-formed steel, including a thin profile and problematic joints. Especially in the cantilever structure, it is necessary to analyze because the maximum deflection that occurs in the cantilever structure has a greater value than the simple supported beam structure. This study aims to study the effect of load on deflection in each type of cold rolled steel beam-column connection. The results of this study were obtained for the average maximum load that can be resisted at the screw connection variation is 1.26 kN, the screw-gusset plate connection is 1.43 kN, the screw-angle cleats connection is 1.92 kN, and at the screw-plate gusset-angle cleats connection is 1.60 kN and for the average value of the deflection that occurs at the maximum load on the screw connection is 28.67 mm, at the screw-plate gusset connection is 58.99 mm, the deflection at the screw-angle cleats connection is 22.44 mm, and the deflection at the screw-plate gusset-angle cleats connection is 49.67 mm. From these data, it was found that the experimental load-deflection value relationship did not reach the analytical load-deflection value. At the screw connection the damage that occurs is a tear in the connection plate (tear out), at the gusset plate connection the damage that occurs is the collapse of the gusset plate, at the screw-angle cleats connection the damage that occurs is 2, where the damage starts with a tear in the connection plate ( tear out) and followed by damage to the screw that was damaged pull out (pull out),Keywords: Flexural strength, deflection, failure pattern, cold rolled steel.